SEMINARY FORMATION PROGRAMS AND QUALITY OF LIFE OF PIANS - Aguason, Fr. Anthony O. (President University, 2024)
The study investigated the extent of efficacy of the formation program of St. Pius X Seminary (SPXS) and its effect on the degree of the quality of life of PIANS. The respondents of the study were the 320 PIANS selected PIANS. The study was a descriptive-correlational research. A researcher-made questionnaire was used in data gathering. Frequency count, percentage, mean, t-test, ANOVA, tukey HSD post hoc test and Pearson-r were the statistical tools used to analyze and interpret the gathered data. Results indicated that the extent of efficacy of the seminary formation program as a whole was rated excellent in terms of human formation, spiritual formation, intellectual formation and pastoral formation. The degree of the quality of life of PIANS as a whole was also rated excellent in terms of Church involvement, sociopolitical life, professional life and family life. Age and type of respondent are factors that indicate a significant difference in the efficacy of the seminary formation program. On the other hand, the respondents’ income and years spent at SPXS show no significant difference. Civil status is a factor that indicates a significant difference in the degree of the quality of life of PIANS. Yet, the age, type of respondent, monthly income and number of years spent at SPXS show no significant difference. Finally, the study reveals that the degree of the PIANS’ quality of life is being influenced by their seminary formation.